Feline Infectious Peritonitis with Distinct Ocular Involvement in A Cat in Turkey - Baydar, Ersoy; Eroksuz, Yesari; Timurkan, Mehmet Ozkan; Eroksuz, Hatice (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
An approximately 2-year old domestic short hair female cat weighting 2.750g was presented to Firat University Veterinary Teaching Hospital with a history of depression, anorexia and weight loss for the last 15 days. Clinical examination revealed incoordination, hyperaesthesia, circling, head tilt, posterior paraparesis, absence of the pupillary reflex in both eyes, opisthotonus and anisocoria. Blood samples were examined for hematological, RT-PCR and biochemical analyses. The cat died without any improvement of clinical findings although symptomatic treatment was made. Necropsy revealed that distinct ocular lesions such as hyphema and thick proteinous exudate accumulation in vitreous in both eyes. Microscopically; there was pyogranulomatous vasculitis in meninges, sclera, corpus ciliare choroid, retina was partially detached in the right eye with retinal epithelial hypertrophy. The kidneys contained focal subcapsular, gray to yellow raised nodules varying from 3 to 10 mm in diameter, and there was discrete fatty degeneration in the liver. The RT-PCR revealed that RNA for FCoV was positive in the blood sample. As a result; the non-effusive form of FIP with distinct ocular involvement was diagnosed through clinical, pathological and polymerase chain reaction (PCR) findings.
Türkiye’de bir kedide göz lezyonlarıyla belirgin feline enfeksiyöz peritonitis olgusu
Keywords: Anisocoria; Cat; Eye; Feline infectious peritonitis; Hyphema